A Study of Augmentativization in English and Bangla - Morshed, Sarwar (University of Muhammadiyah Prof. DR. HAMKA, 2018)
Augmentativization refers to the processes of formation of words denoting largeness. In this study, the researcher has juxtaposed English and Bangla vis-à-vis their mechanisms in the construction of augmentatives. The present research reveals that the languages under this study have striking similarities in the process of augmentativization. Both the languages use affixation in the construction of augmentatives. Curiously, the two languages employ prefixation to form the bulk of their augmentative vocabulary. Suffixation in augmentativization is very marginal in both the languages. Apart from affixation, the two languages employ compounding to form augmentatives. Still, the two tongues have another category of augmentatives known as frozen or lexicalized augmentatives.  The catalogue of identical processes used in the construction of augmentatives does not end here. Borrowing is a good source of augmentative vocabulary in both the languages. English and Bangla have borrowed augmentatives or augmentative markers from foreign sources. Gradation of augmentatives is also possible in both the languages. Keywords: augmentative, augmentizer, frozen augmentative, morphological augmentative, pragmatic function.